Respon Pertumbuhan Stek Batang Sirih Merah (Piper crocatum Ruiz dan Pav). setelah Direndam dalam Urin Sapi - Mukarlina, Lusiana, Riza Linda, (Jurnal Protobiont, 2013)
Red bettle (Piper crocatum Ruiz and Pav) was one kind of plants that was used as an ornamental plant and medicine. Red bettle plant was propagated using stem cutting. Propagation by stem cuttings was often failed because of the absence of root growth. Natural plant growth regulator was used to address that failure. One of plant growth regulators which may affect the growth of red bettle was cow urine. The aimed of this study at finding the effect of cow urine intake on the rad betel stem cutting and determining the effect of cow urine on the growth of red bettle stem cuttings as well as the best time of soaking. The research was conducted in the department of Biology of Mathematics and Natural Sciences faculty Tanjungpura University Pontianak from July to September 2012 using a Completely Randomized Desigen (CRD) with factorial pattern that consists of 2 treatment factors. The first factor was the concentration of cow urine the second factor was the time of immersion. Concentration of cow urine is used 0%, 5%, 10%, 15%. Soaking time used was 0 minute, 15 min, 30 min, 45 minute. Each treatment was repeated three times so that there would be 48 treatment units. The results showed that the treatment of 15% cow urine for 45 minute soaking was the best combination for the growth of stem cuttings red bettle.